If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -12 = -10 + 4m Reorder the terms: -12 + 5m = -10 + 4m Solving -12 + 5m = -10 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. -12 + 5m + -4m = -10 + 4m + -4m Combine like terms: 5m + -4m = 1m -12 + 1m = -10 + 4m + -4m Combine like terms: 4m + -4m = 0 -12 + 1m = -10 + 0 -12 + 1m = -10 Add '12' to each side of the equation. -12 + 12 + 1m = -10 + 12 Combine like terms: -12 + 12 = 0 0 + 1m = -10 + 12 1m = -10 + 12 Combine like terms: -10 + 12 = 2 1m = 2 Divide each side by '1'. m = 2 Simplifying m = 2
| -36-b-4b=64 | | 5m+1=-23 | | 11.3-7.2=-3.82 | | 1.3-7.2=-3.82 | | 8.4s-s=14.8 | | -5z+3z-7=8z-1-6 | | 3x-2=4x-8 | | 7n^2-43n+6=0 | | n^2=n | | 7p^2-27p-40=0 | | 5a=20 | | -7=2y-3-3y | | 3x-7(-2x+8)=-5 | | 3x-7y=-5 | | 10n+8p=0 | | S=3t+40 | | (x-1)+(x+3)=2x | | k-8(7+k)=-1(5) | | 4t-3-3t=-5 | | 9x+3y=4 | | (3x+4)(2-5x)=0 | | c=(2)(3.14)(r) | | 9x-4y=-2 | | 6.3y=4.1y+12 | | 1.2=1.6m | | c=23 | | -8=5a-3a | | -54=133.578499968x+0.5*0.0209625668*17843.21565 | | 6(x+2)-(3x-8)= | | 4(x+3)-(2x-4)= | | 54=133.578499968x+0.5*0.0209625668*17843.21565 | | 3b+(4b-6b+2)-b=10 |